Assessment of Mangrove Replanting Site at Kg Tanjung Kepah, Lekir, Perak - Mohd Fauzi, N.F. (IOP Publishing Ltd, 2020)
Mangroves are formation of salt-tolerant shrubs that inhabit the inter-tidal zones of sheltered coasts like estuaries and lagoons in tropical and subtropical latitudes. They solidly secure the land from the seas, and have the capability of withstanding strong wave action and heavy storm surges. The effectiveness of mangroves as natural coastal protection buffer has been well proven in the 2004 Indian Ocean Tsunami that brought devastating economic and ecological impacts to thirteen Asian and African countries, including Malaysia. Despite the importance of mangroves in coastal protection, this intertidal vegetation has been reported to be depleted at an alarming annual rate of 1 to 2 globally due to impacts of natural processes and anthropogenic influences. Tremendous efforts of mangrove restoration have been implemented along the Malaysian shoreline in the past decade, but just a modest number have been planned or studied by environmentalists and other researchers. The plantings were mostly executed in a trial-and-error approach without having a full understanding of the site conditions. Hence, a thorough appreciation of the site condition is mandatory so as to ensure high survivability of the young mangrove saplings at the replanting sites. This paper aims to assess one of mangrove replanting sites in Malaysia which is located at Kg Tanjung Kepah, Lekir, Perak. Several mangrove replanting efforts have been undertaken by Forestry Department at the area. However, none of the mangrove seedlings survived three months after the plantation at the open area sites. Some assessment were conducted including mangrove tree assessment, current measurement, soil and water sampling as well as topography detailed survey. The analysis from the assessment shows that the mangrove replanting failures might be influenced by several possible factors, especially the shore slope and topography. Hence, the most suitable engineering approach will be suggested for future protection. Â© Published under licence by IOP Publishing Ltd.